(untitled) (Global Journal of Science Frontier Research, 2019)
In this paper, Galerkin method is presented to obtain the approximate solutions of the system of second order boundary value problems using piecewise continuous and differentiable Bernstein polynomials. Derivation of rigorous matrix formulations is exploited to solve the system of second order boundary value problems where, given boundary conditions are satisfied by Bernstein polynomials. The derived formulation is applied to solve the system of second order boundary value problems numerically. Results of numerical approximate solutions converge to the exact solutions monotonically with desired large significant accuracy.